Pengembangan Bahan Ajar Digital Berbasis Flipbook Interaktif pada Materi Hak dan Kewajiban Siswa Sekolah Dasar - Ayudia, Inge; Saputri, Lhutfia Wahyu; Munthe, Sediken Tara (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The development of digital technology encourages teachers to create innovative learning media that are suitable for the characteristics of elementary school students. One subject that is still often taught conventionally is the topic of rights and responsibilities in the Pancasila education subject. This study aims to develop an interactive flipbook as a digital teaching material for elementary school students. The research uses the Research and Development (R&D) method with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects are fifth-grade elementary school students. Data collection techniques are carried out through interviews, observations, questionnaires, and validation sheets from material experts as well as media experts. The research results indicate that the interactive flipbook received a very feasible category from content experts and media experts. Teacher and student responses also showed positive results because the media is engaging, easy to use, and helps students understand the material better. Thus, the interactive flipbook can be used as an alternative digital teaching material in Pancasila education learning in elementary schools. This study is still limited to one school and one learning material, so the research results cannot yet be widely generalized. Therefore, it is recommended that further research develop interactive flipbooks for other materials and test their effectiveness on student learning outcomes with a broader scope.